Electrophysiological Detection of Intracochlear Scalar Changing Perimodiolar Cochlear Implant Electrodes: A Blinded Study. Issue 7 (August 2015) - Mittmann, Philipp; Todt, Ingo; Wesarg, Thomas; Arndt, Susan; Ernst, Arneborg; Hassepass, Frederike
Abstract : Objective: To investigate whether a previous established neural response telemetry (NRT) ratio corresponds with the scalar position of the CI electrode. Study Design: Retrospective blinded controlled study. Setting: Tertiary referral center. Patients: The electrophysiological data sets of 85 patients with measured intraoperative NRTs were evaluated. All patients were implanted with the same CI system. Using a flat panel tomography system, the position of the electrode array was confirmed radiologically. Interventions: The radiological results were blindly compared with the intraoperatively obtained electrophysiological data (NRT ratio) and statistically evaluated. In a second step, irregularities between the NRT ratios and the radiologically confirmed electrode positions were determined and the entire study material was investigated deeper. Main Outcome Measures: Correlation of the NRT ratio with the intracochlear position of the CI electrode. Results: By electrophysiological evaluation only, 69 patients were detected without a scalar change at first. In 16 patients, a scalar change was probable. A significant correlation between the radiological results and the NRT ratios was found. Secondly, additional patient characteristics were identified which influences the electrode's position. Excluding those patients, the selectivity and specificity of the NRT ratio could be increased to a higher level. Conclusion: Evidenced by a blinded group of patients, we are able to show that the electrode array position within the cochlea could be predicted using the NRT ratio.